Desenvolvimento de requeijão cremoso com baixo teor de lactose produzido por acidificação direta e coagulação enzimática - Mattanna, Paula (2011)
Much of the world population has problems in consuming milk and dairy products because some people are lactose intolerant. To be absorbed in the intestine lactose needs to be hydrolyzed by lactase enzyme. People with lactose intolerance do not produce lactase and therefore can not enjoy milk and dairy products benefits. This work aim to prepare requeijões cremosos by two different processes (direct acidification and enzymatic coagulation) by adding lactase enzyme at different concentrations (0.2; 0.5 and 0.8 g of lactase enzyme per liter of milk, respectively) and evaluating their physico-chemical, microbiological and sensory properties compared with requeijões control sample. In relation to physical and chemical characteristics the requeijões prepared are in accordance with current law. The lactose was hydrolyzed in more than 70 % for the treatments with adding of the lactase enzyme, enough to alleviate symptoms of intolerance in people who not well absorb lactose. Lactose found in "requeijões" with added lactase are considered low, within the standards regulated by the laws of foods for special purposes. The requeijões were sensoring accepted, no difference was detected statistic by Tukey test (p<0.05) in testing by a hedonic scale among treatments. The lipid profile of requeijões , the total saturated fatty acids ranged from 62.76% to 64.70%, while total unsaturated ranged from 34.36% to 38.36%. In the texture profile analysis only the firmness and elasticity parameters differed significantly (p< 0,05) during the storage period (60 days). Considering the results it is possible conclude that the enzyme lactase used in the experiment efficiently hydrolyzed the lactose of the requeijões , and, did not affect the physico-chemical and sensory characteristics of the product, then this is a viable option for the lactose intolerant people.